2020
DOI: 10.3390/molecules25235569
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Molecular Docking of Paracyclophanyl-Thiazole Hybrids as Novel CDK1 Inhibitors and Apoptosis Inducing Anti-Melanoma Agents

Abstract: Three new series of paracyclophanyl-dihydronaphtho[2,3-d]thiazoles and paracyclophanyl-thiazolium bromides were designed, synthesized, and characterized by their spectroscopic data, along with X-ray analysis. One-dose assay results of anticancer activity indicated that 3a–e had the highest ability to inhibit the proliferation of different cancer cell lines. Moreover, the hybrids 3c–e were selected for five-dose analyses to demonstrate a broad spectrum of antitumor activity without apparent selectivity. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Based on the data from the literature [138][139][140] as well as on their previous results [141], Aly et al [142] designed and synthesized a novel series of derivatives incorporating three bioactive entities such as 1,4 dihydronapthoquinone, thiazole, and [2.2] In order to elucidate the potential mechanism of action of synthesized compounds, the docking studies were carried out against three potential targets, protein kinases CLK1 (5 × 8I), EGFR (2J5F), and tubulin (1SA0). The best docking score was found against CLK1 and binding energy (−9.264 to −8.794 kcal/mol) and was in accordance with anticancer activity.…”
Section: Thiazole Derivatives As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data from the literature [138][139][140] as well as on their previous results [141], Aly et al [142] designed and synthesized a novel series of derivatives incorporating three bioactive entities such as 1,4 dihydronapthoquinone, thiazole, and [2.2] In order to elucidate the potential mechanism of action of synthesized compounds, the docking studies were carried out against three potential targets, protein kinases CLK1 (5 × 8I), EGFR (2J5F), and tubulin (1SA0). The best docking score was found against CLK1 and binding energy (−9.264 to −8.794 kcal/mol) and was in accordance with anticancer activity.…”
Section: Thiazole Derivatives As Anticancer Agentsmentioning
confidence: 99%
“…Based on the data from the literature [138][139][140] as well as on their previous results [141], Aly et al [142] designed and synthesized a novel series of derivatives incorporating three bioactive entities such as 1,4 dihydronapthoquinone, thiazole, and [2.2] paracyclophane in the frame of one molecule 88a-e, 89a-d, 90 (Figure 35). Compounds 88a-e displayed the highest inhibition of proliferation of different cancer cell lines, showing a broad spectrum of anticancer activity against nine tumor subpanels in an in vitro five dose full NCI 60-cell panel assay.…”
Section: Thiazole Derivatives As Anticancer Agentsmentioning
confidence: 99%
“…The ability of a bioactive compound to quench activities that lead to abnormal cell growth has been applied in the treatment of inflammatory-related diseases. Five highly reactive naphthoquinones ( 89 – 93 ) investigated by Aly et al showed promising anti-tumor activity via cell cycle arrest in the pre-G1 and G2/M phases and downregulation of cyclin-dependent kinases (CDK) [ 136 ]. Three of them, 91 – 93 were found to be strong inhibitors of cyclic dependent kinases with 91 being the most potent.…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%
“…Three of them, 91 – 93 were found to be strong inhibitors of cyclic dependent kinases with 91 being the most potent. Compound 91 attenuated eight isoforms of CDK and phosphor-tyr15 and also induced apoptosis and cell cycle arrest by downregulating pre-G1 and G2/M phases, respectively [ 136 ].…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%
“… 6 Among the following three assigned series I − III of the synthesized paracyclophanyl-heterocycles ( Figure 1 ), series I having 1,4-dihydronaphthoquinone, was found as more active as antiproliferative agents than their naphthalene-containing congeners (series II and III) toward the SK-MEL-5 melanoma cell line. 6 …”
Section: Introductionmentioning
confidence: 99%